2023
DOI: 10.1186/s12888-023-04583-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with anxiety and depression among community-dwelling older adults in Hunan, China: a cross-sectional study

Abstract: Background Older adults’ psychological health is a public health issue that cannot be ignored, especially when these psychological health problems and related factors change across different social backgrounds because of rapid changes in traditions and family structures and the epidemic responses after the outbreak of COVID-19 in China. The aim of our study is to determine the prevalence of anxiety and depression and their associated factors among community-dwelling older adults in China. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 50 publications
3
13
0
1
Order By: Relevance
“…43 In this study, it was observed that elderly individuals who engaged in regular daily walks experienced lower levels of anxiety. This finding aligns with the results of studies conducted by Lu L et al, and Sirin et al 40,45 Exercise, particularly through activities like daily walking, stands out as one of the most important and accessible methods to manage anxiety among the elderly. Engaging in physical activity, increasing social interactions, and fostering an active lifestyle can yield several benefits, including enhanced self-esteem, increased empowerment, reduced mental stress, improved physical and mental health, boosted immunity, and redirection of attention away from anxiety-inducing stimuli.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…43 In this study, it was observed that elderly individuals who engaged in regular daily walks experienced lower levels of anxiety. This finding aligns with the results of studies conducted by Lu L et al, and Sirin et al 40,45 Exercise, particularly through activities like daily walking, stands out as one of the most important and accessible methods to manage anxiety among the elderly. Engaging in physical activity, increasing social interactions, and fostering an active lifestyle can yield several benefits, including enhanced self-esteem, increased empowerment, reduced mental stress, improved physical and mental health, boosted immunity, and redirection of attention away from anxiety-inducing stimuli.…”
Section: Resultssupporting
confidence: 90%
“…The findings of this study demonstrate that comorbidity contributes to increased anxiety among the elderly, which is in line with the results of previous research by Lu L et al ., Raeisvandi et al ., Cho et al ., and Wang et al 10,39–41 . The elderly participants in Zhang's study (2023) had an average of 4.1 diseases, with one‐fifth of them experiencing six or more concurrent illnesses.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This was consistent with the results of a study that investigated the bidirectional relationship between insomnia, depression, and anxiety among 625 participants who complained of strong anxiety where 62% were women, and of the 416 participants who complained of high levels of depression, 60% were female [7]. In general, depression/ anxiety increases with age, and according to a cross-sectional study conducted in China, women experience more anxiety and depression than men, and patients with low education or low income experience higher levels of depression and anxiety, especially older adults [20]. However, the results of this study showed that it was different in insomnia patients, therefore, it can be speculated that younger people suffer more from insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, older adults have a higher prevalence of mental disorders compared to younger people (Andreas et al 2017). Among these disorders, depression and anxiety are common among the elderly, with incidence rates exceeding 30% (Lu et al 2023). Geriatric depression (McCall and Kintziger 2013) and anxiety (Yang et al 2021) have become important public health concerns.…”
Section: Introductionmentioning
confidence: 99%